ANALISIS PENGARUH FINANCIAL DISTRESS, LEVERAGE, PROFITABILITAS, DAN PERTUMBUHAN PERUSAHAAN TERHADAP TAX AVOIDANCE PADA PERUSAHAAN SUB SEKTOR WHOLESALE YANG TERDAFTAR DI BEI TAHUN 2018-2020 - Fitri Riski Riyadi; Nurjanti Takarini (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
One source of state revenue is obtained from taxes. Taxes are the main contributor to state revenue. Several factors are thought to influence the practice of tax avoidance by companies, including financial distress, leverage, profitability, and company growth. This study aims to analyze the effect of financial distress, leverage, profitability, and company growth on tax avoidance in wholesale sub-sector companies listed on the Indonesia Stock Exchange in 2018-2020. The population in this study amounted to 44 companies with a sample of 26 companies. The research data is secondary data in the form of financial statement data listed on the Indonesia Stock Exchange for the 2018-2020 period. The method of determining the sample in this study used a purposive sampling method with multiple linear regression analysis techniques. Simultaneously, financial distress, leverage as proxied by DER, profitability as proxied by NPM, and company growth as proxied by sales growth have a positive effect on tax avoidance. Partially, financial distress, leverage as proxied by DER, and profitability as proxied by NPM do not affect tax avoidance. while the company's growth as proxied by sales growth has a significant positive effect on tax avoidance.